2006
DOI: 10.1529/biophysj.106.084228
|View full text |Cite
|
Sign up to set email alerts
|

Internal Structure of Chlorosomes from Brown-Colored Chlorobium Species and the Role of Carotenoids in Their Assembly

Abstract: Chlorosomes are the main light harvesting complexes of green photosynthetic bacteria. Recently, a lamellar model was proposed for the arrangement of pigment aggregates in Chlorobium tepidum chlorosomes, which contain bacteriochlorophyll (BChl) c as the main pigment. Here we demonstrate that the lamellar organization is also found in chlorosomes from two brown-colored species (Chl. phaeovibrioides and Chl. phaeobacteroides) containing BChl e as the main pigment. This suggests that the lamellar model is universa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
46
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 24 publications
3
46
0
1
Order By: Relevance
“…A similar selfassembled aggregate can form in the absence of proteins and exhibits spectral and excitonic properties similar to those of pigments in the native chlorosomes (for a review, see reference 3). The BChl aggregates were suggested to form lamellar structures in chlorosomes of green sulfur bacteria with lamellar spacing between 2 and 3 nm, depending on the main BChl (BChl c or e) and the prevailing esterifying alcohol (38,39). In this model, the lamellar layers are maintained by nonspecific hydrophobic interactions of the interdigitated esterifying alcohols, while the in-layer arrangement is mediated through specific interactions between the stacked chlorin rings.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…A similar selfassembled aggregate can form in the absence of proteins and exhibits spectral and excitonic properties similar to those of pigments in the native chlorosomes (for a review, see reference 3). The BChl aggregates were suggested to form lamellar structures in chlorosomes of green sulfur bacteria with lamellar spacing between 2 and 3 nm, depending on the main BChl (BChl c or e) and the prevailing esterifying alcohol (38,39). In this model, the lamellar layers are maintained by nonspecific hydrophobic interactions of the interdigitated esterifying alcohols, while the in-layer arrangement is mediated through specific interactions between the stacked chlorin rings.…”
mentioning
confidence: 99%
“…It has been proposed that this arrangement improves the absorption of photons with different polarizations (39). This, together with aggregation-induced enlargement of the oscillator strength, enables the bacteria to survive under extremely low-light conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the structural organization of the BChl molecules in all chlorosomes may be similar (4,22,25,37,38), with the exception of CsmA, the composition and sequences of the envelope proteins of chlorosomes of the phyla Chlorobi, Chloroflexi, and Acidobacteria are not well conserved. Blankenship (1) suggested that lateral gene transfer might have been responsible for the presence of the genes for chlorosome biogenesis among some of these three groups of bacteria.…”
mentioning
confidence: 99%